2012
DOI: 10.1007/s00706-012-0781-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of fused uracils: pyrano[2,3-d]pyrimidines and 1,4-bis(pyrano[2,3-d]pyrimidinyl)benzenes by domino Knoevenagel/Diels-Alder reactions

Abstract: Knoevenagel condensation of barbituric acids with aromatic aldehydes containing one or two formyl groups was carried out. 5-Arylidenebarbituric acids underwent smooth hetero-Diels-Alder (HDA) reactions with enol ethers to afford cis and trans diastereoisomers of pyrano[2,3-d]pyrimidine-2,4-diones and 5,5′-(1,4-phenylene)bis[2H-pyrano[2,3-d]pyrimidine-2,4(3H)-dione] derivatives in excellent yields (75–88 %). Syntheses were realized by Knoevenagel condensation and HDA reaction in four different reaction conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…After immense literature survey, it was found that catalyst free synthesis of pyrido[2,3‐ d ]pyrimidine has not been reported till date . Thus to carry onward our research program of designing green synthetic strategies to important heterocyclic molecules, we herein report a new, metal free, clean and efficient one‐pot synthesis of Pyrano[2,3‐ d ]pyrimidine using ethylene glycol as a promoting medium (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…After immense literature survey, it was found that catalyst free synthesis of pyrido[2,3‐ d ]pyrimidine has not been reported till date . Thus to carry onward our research program of designing green synthetic strategies to important heterocyclic molecules, we herein report a new, metal free, clean and efficient one‐pot synthesis of Pyrano[2,3‐ d ]pyrimidine using ethylene glycol as a promoting medium (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…40 Then, the alkyne 4a was synthesized through the Knoevenagel condensation of barbituric derivative 3a and propargylated hydroxybenzaldehyde 2a under reflux conditions in good yield (Scheme 2b and Table I). 41,42 The general procedure for the preparation of organic azides is shown in Scheme 2c. 39 Then the cycloadduct 7 was prepared from the [3+2] CA reaction of benzyl azide 6a as a dipole and alkyne 4a as a dipolarophile in the presence of copper(I) species, generated in situ from copper(II)/ascorbate in DMSO.…”
Section: Resultsmentioning
confidence: 99%
“…The dipolarophiles 8 were synthesized by the reaction of thiazolidinone 3 with propargylated salicylaldehyde 5 and malononitrile as a catalyst under reflux in good yield. Then, dipolarophile 8 was formed through a Michael addition reaction between the active CH 2 group of the 4-thiazolidinones 3 with the C¼C bond of malononitrile arylidene (Scheme 3) [58,59].…”
Section: Methodsmentioning
confidence: 99%
“…In 2009, Khoshkholg and coworkers [76] described a one-pot reaction to form 6H-Indeno[2 0 ,1':5,6]pyrano [3,4-c]chromen-13(13bH)-one under a CA reaction to give the corresponding pyran. In 2012, Pałasz also reported a multi-component, one-pot reaction for pyrano [2,3-d] pyrimidine derivative synthesis through domino Knoevenagel/Diels-Alder reactions [59]. Accordingly, we had planned the synthesis of N-phenyl-6H,11bH-chromeno [4 0 ,3':4,5] pyrano [2,3-d] thiazol-2-amine 12 from an intramolecular hetero Diels-Alder (HAD) reaction of α,β-unsaturated carbonyl compound 8a (Scheme 4).…”
Section: Methodsmentioning
confidence: 99%